A Brand Shop como ferramenta midiática e sua influência na experiência de compra: a loja-conceito da apple na mediação entre marca e consumidor - Santini, André Luís (2014)
The theme that guides this research is structured in relation Communication and Consumption and has its corpus the Brand Shop (or Store Concept), a channel used by companies to establish an experiential relationship between brands and consumers . The objective of the study is to demonstrate of media’s role at Brand Shop in the universe of marketing communication, on the relationship between brand and consumer, even with his ambivalent role of business and communication agent. The rapprochement between customer and product offered by this channel during the shopping experience provides reflections related to the fact that consumer goods also give visibility and can still carry a social significance because of a cultural focus of analysis in its use as communicators. The study seeks to prove the hypothesis that Brand Shop can be considered a media tool in analogy to other communication means used for moving a message; and also for its ability to brand building through its mediating role, adding to a menu of communication tools with a focus on maximizing competitive advantages of companies and products. The research makes use of the Apple Store as an empirical object. The methodology proposed in this project involves an exploratory empirical study with semi-structured interviews , whose focus is the search for understanding of the channel and its communicational influence , coupled with a literature whose theoretical frameworks ranging from Pedro Gomes and Sá Martino to a better understanding of the models communication; spend by looking into the relationship between subject, object and consumption with authors such as Silverstone , Miller , and Douglas Bauman and permeates the mediation as a premise for persuasion with France and Barbero . Communication concepts and theories add up to mercantile references to authors like Kotler , Shimp , Rosenbloom and Yanaze .